The Effect of Communication and Decision-Making on Teacher Performance in Junior High School - Rosyida, Ida; Syarifudin, Syarifudin (Universitas Negeri Yogyakarta, 2023)
This study aims to determine: (1) the effect of the principal's communication on teacher performance; (2) the effect of the principal's decision making on teacher performance; and (3) the effect of the principal's communication and the principal's decision-making simultaneously on teacher performance. This research uses a quantitative approach with a survey method. The population is teachers in Public Junior High School (PJHS) 2 of Tangse Sub district, Pidie District, Aceh Province. The proportional random sampling technique determined a sample of 22 teachers with a population of 25 people. Data collection used a questionnaire. Test the validity and reliability of the instrument using the product moment statistical test, which was carried out with the help of SPSS 20. The analysis prerequisite tests consisted of normality, correlation, and simple regression tests. The results of this study are as follows: (1) There is an effect of the principal's communication on teacher performance at PJHS Tangse 2 with a percentage of 26.2% (2) There is an effect of the principal's decision making on teacher performance at PJHS 2 Tangse with a percentage of 26.7 (3) There is an effect of the principal's communication and principal's decision-making on teacher performance at PJHS Tangse 2 with a percentage of 49.2%